2004
DOI: 10.1021/jf034773t
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Essential Oil of Leaves, Galls, and Ripe and Unripe Fruits of Jordanian Pistacia palaestina Boiss.

Abstract: Pistacia palaestina Boiss. (Pistacia terebinthus L. var. palaestina (Boiss.) Engl.) is a medicinal and foodstuff plant. The ripe fruits are used largely in the Middle East as a component of the so-called Zaatar, a mix of aromatic and food plants. Results of GC and GC-MS analyses of the essential oils of leaves, galls produced by Baizongia pistaciae (L.), and ripe and unripe fruits of Pistacia palaestinaBoiss. collected in Jordan are reported. Both qualitative and quantitative differences between different part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 27 publications
(32 reference statements)
0
25
0
Order By: Relevance
“…All four species contain α-pinene, ranging from 3.8 % to 15.6 %, while terpinolene is found in concentrations ranging from 0.1 % to 6.9 %. It should be noted that Pistacia terebinthus is characterized by an elevated concentration of limonene (34.2 %) [22], Pistacia atlantica is characterized by an elevated concentration of bornyl acetate (21.5 %) [23], Pistacia lentiscus contained as major components myrcene (68.2-71.0 %) and limonene (9.6-19.7 %) [24] and Pistacia palaestina is characterized by an elevated concentration of (E)-ocimene (41.3 %) and sabinene (20.3 %) [25]. All the major components of the related species are found in P. vera in concentrations amounting to less than 2.5 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All four species contain α-pinene, ranging from 3.8 % to 15.6 %, while terpinolene is found in concentrations ranging from 0.1 % to 6.9 %. It should be noted that Pistacia terebinthus is characterized by an elevated concentration of limonene (34.2 %) [22], Pistacia atlantica is characterized by an elevated concentration of bornyl acetate (21.5 %) [23], Pistacia lentiscus contained as major components myrcene (68.2-71.0 %) and limonene (9.6-19.7 %) [24] and Pistacia palaestina is characterized by an elevated concentration of (E)-ocimene (41.3 %) and sabinene (20.3 %) [25]. All the major components of the related species are found in P. vera in concentrations amounting to less than 2.5 %.…”
Section: Resultsmentioning
confidence: 99%
“…GC-MS analyses were also performed on a Finnigan Trace GC-MS with an external ion source in both the EI and chemical ionization (CI) modes at a flow rate of 1.0 mL/min, using CH 4 as the CI ionization reagent. The identification of the compounds (Table 1) was based on comparison of their retention indices (RI), obtained using n-alkanes (C 8 -C 25 ), and comparison of their EI-mass spectra with the NIST/NBSWiley library spectra and literature data [26]. Additionally, the identity of all compounds was confirmed by comparison of the expected molecular weights with the results obtained from the CI spectra and in several cases by co-injection with available authentic samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the essential oil of unripe fruits from P. terebinthus of Turkish origin, limonene (34.2%), α-pinene (15.6%) and β-pinene (11.5%) were reported as the major constituents, 14 while in P. atlantica myrcene, sabinene and terpinen-4-ol were detected as the main compounds. In a recent study, Flamini et al 15 reported on the chemical composition of P. palaestina (closely related to P. terebinthus, and considered by some botanists as a subspecies or variety of it); the main compounds in the leaf oil were α-pinene (63.1%) and myrcene (13.3%) and in unripe fruit oil (E)-ocimene (41.3%) and sabinene (20.3%). The vast amount of literature deals with the chemical composition of P. lentiscus essential oils, where a considerable variability in the terpene composition is also observed.…”
Section: Resultsmentioning
confidence: 99%
“…This kind of herbivore spends a major part of its life cycle into the plant tissues 10 and apparently do not have behavioral strategies to avoid the effects of the plant defensive metabolites. Among a few published works related to signaling between insect gall makers and their hosts, Flamini and coworkers 11 reported changes in volatile composition of Pistacia palaestina Boiss (Anacardiaceae) under the attack of Baizongia pistaciae (Homoptera: Aphidoidea).…”
Section: Introductionmentioning
confidence: 99%
“…6,11 Psyllids are very tiny species and are obligatory parasites, i.e., need the plant hosts in the majority of its life cycle. 26 Traditional chemoecological tests are not appropriate to investigate these galling species.…”
mentioning
confidence: 99%